2000
DOI: 10.1053/jlts.2000.18492
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary heterotopic liver transplantation with portal vein arterialization for fulminant hepatic failure

Abstract: Auxiliary liver transplantation for patients with fulminant hepatic failure supports the patient's failing liver for a period of time until the native liver (NL) has recovered and immunosuppression can be withdrawn. Auxiliary heterotopic liver transplantation (AHLT) with portal vein arterialization (PVA) has several advantages over auxiliary orthotopic liver transplantation: NL resection is not required, and the hepatic hilum is left untouched; thus, the chances of liver regeneration are optimal. The successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…The recognition of the importance of portal blood to liver homeostasis and regeneration was obviously crucial to the pioneers of liver transplantation as they observed how the auxiliary graft would undergo atrophy without portal blood constituent stimulus [18]. The earlier canine and porcine PVA experiments [10,11,12,13,14,63,64,65] also illustrated to the transplantation surgeon that the auxiliary graft could be perfused by PVA as an option to leave the hilus of the native liver untouched and also in cases of portal vein thrombosis [94,95,96,97]. Could PVA of the small-for-size graft be an option in the future to avoid the small-for-size syndrome?…”
Section: The Benefits Of 133 Years Of Surgical Research On Liver Regementioning
confidence: 99%
“…The recognition of the importance of portal blood to liver homeostasis and regeneration was obviously crucial to the pioneers of liver transplantation as they observed how the auxiliary graft would undergo atrophy without portal blood constituent stimulus [18]. The earlier canine and porcine PVA experiments [10,11,12,13,14,63,64,65] also illustrated to the transplantation surgeon that the auxiliary graft could be perfused by PVA as an option to leave the hilus of the native liver untouched and also in cases of portal vein thrombosis [94,95,96,97]. Could PVA of the small-for-size graft be an option in the future to avoid the small-for-size syndrome?…”
Section: The Benefits Of 133 Years Of Surgical Research On Liver Regementioning
confidence: 99%
“…Such a situation always requires complicated vascular reconstruction, and is associated with a considerably increased peri-operative risk [15]. Aimed, nevertheless, at achieving adequate perfusion of the transplant even in such a situation, complete arterialization of the portal vein (PVA) has recently been propagated as a technically relatively simple procedure [2,4,5,6, 141. Some authors have also reported that PVA can also be employed in auxiliary liver transplantations [4,6,131.…”
Section: Introductionmentioning
confidence: 99%
“…Aimed, nevertheless, at achieving adequate perfusion of the transplant even in such a situation, complete arterialization of the portal vein (PVA) has recently been propagated as a technically relatively simple procedure [2,4,5,6, 141. Some authors have also reported that PVA can also be employed in auxiliary liver transplantations [4,6,131. Experience with the few patients that have undergone transplantation by this technique has been interpreted as a demonstration of both the technical feasibility of PVA and the regular initial function of the transplant [2,3,4,5,6,7,141.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is less postoperative bleeding and more remaining liver mass for bridging (graft) and regeneration (native liver). The clinical results demonstrated that sufficient liver function can be achieved using this technique [3,4].…”
Section: Introductionmentioning
confidence: 91%